The Health of Aging Hispanics The Mexican-Origin Population - Angel, Jacqueline L.; Whitfield, Keith E. (Springer New York : Imprint: Springer, 2007)
The Health of Aging Hispanics: The Mexican-Origin Population edited by Jacqueline L. Angel University of Texas at Austin, Austin, Texas and Keith W. Whitfield Pennsylvania State University, University Park, Pennsylvania The population of the United States, like that of most other nations, will age rapidly well into the 21st century. By 2025, at least one-fifth of the population in 15 countries in the Americas is to be age 60 or over. Additionally, as the result of high immigration and fertility rates, as well as improvements in life expectancy, the United States Census Bureau projects that by 2050, the total number of non-Hispanic white aged 65 and over will more than triple, and the number of Hispanics in this age bracket will increase eleven fold. Despite these demographic facts, there is a significant dearth of information about the unique strengths and characteristics that underrepresented minority possess and experience as they age. Further examination of these understudied groups, especially among Hispanics - now the nation's largest minority group - offers the possibility to promote healthy aging for the entire nation. In this unique volume, contributions provide initial information on numerous factors that affect the health security of Mexican-origin families and individuals as they face the burdens of decline in health status and caring for children and the elderly simultaneously, including health issues before and after immigration. Also included is material addressing important issues related to the contemporary political debate on immigration and healthcare reform in the United States and Mexico. In the coming decades, collections such as this will be critical to develop a better understanding of how immigration from Latin America, Asia and Africa to the United States produces health disparities in our aging population.